2022
DOI: 10.1155/2022/6317008
|View full text |Cite
|
Sign up to set email alerts
|

Pavement Crack Extraction Method from Mobile Laser Scanning Point Cloud

Abstract: The automatic detection of cracks in the road surface is of great significance for maintaining the road surface to ensure the safety of moving vehicles. The Hokuyo UTM 30 LX 2D laser scanner in this study is used to observe the road surface containing two cracks and distress areas. As a result, dense point clouds are created. The road surface is automatically extracted from the point clouds based on the geometry of the two curb lines. The normal vector of the points is calculated based on the principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In this paper, facing the actual needs of 3D reconstruction of building space, aiming at the shortcomings of 3D point cloud data generation, processing and model generation, the 3D reconstruction of building is deeply studied. Visual reconstruction of architectural space has become a key issue in the field of computer vision [9], which has the same high application value as face recognition and target tracking. Three-dimensional reconstruction was first established on the basis of binocular vision, and then developed into multi-view reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, facing the actual needs of 3D reconstruction of building space, aiming at the shortcomings of 3D point cloud data generation, processing and model generation, the 3D reconstruction of building is deeply studied. Visual reconstruction of architectural space has become a key issue in the field of computer vision [9], which has the same high application value as face recognition and target tracking. Three-dimensional reconstruction was first established on the basis of binocular vision, and then developed into multi-view reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…It takes full advantage of efficient machine vision algorithms and avoids complex three-dimensional calculations. However, those approaches miss some edge details of pavement cracks [32][33][34][35][36]. Therefore, some research directly used three-dimensional data exaction for crack detection and demonstrated some successes [31,37,38].…”
Section: Introductionmentioning
confidence: 99%